KESADARAN, PENGETAHUAN DAN PEMAHAMAN SERTA PERSEPSI WAJIB PAJAK SEBAGAI DETERMINAN KEMAUAN MEMBAYAR PAJAK - I Gusti Gde Oka Pradnyana; I Made Purba Astakoni (KRISNA: Kumpulan Riset Akuntansi, 2018)
The aim of this study ; to examine the effect of awareness of paying taxes on the willingness to pay taxes; test the influence of knowledge and understanding on the willingness to pay taxes and test the influence of taxpayer perceptions on the willingness to pay taxes. This research using survey method with closed questionnaire instrument with respondents as much as 62 employees PDAM Tirta Mangutama Badung regency. Analysis of research data using SEM analysis with Partial Least Square (PLS) approach. The results showed the influence of awareness of paying taxes on the willingness to pay a significant positive tax. Means the higher awareness to pay taxes the willingness to pay higher taxes also. The influence of knowledge & understanding of taxpayers on the willingness to pay taxes have a positive effect is not significant on the willingness to pay taxes. The influence of the taxpayer's perception on the willingness to pay taxes on the willingness to pay positive and significant taxes. Means the higher the taxpayer's perception of tax rules the willingness to pay higher taxes as well. Keywords: willingness to pay taxes, awareness of paying taxes, knowledge and understanding of tax regulations, and a good perception of the effectiveness of the tax system.